Living with type 2 diabetes mellitus in the Kingdom of Tonga: a qualitative investigation of the barriers and enablers to lifestyle management - Jennifer Taumoepeau; Catherine R. Knight-Agarwal; ' Esiteli A. P. Tu'i; Rati Jani; Uchechukwu Levi Osuagwu; David Simmons (BMC, 2021)
Abstract Background Despite the increasing prevalence of Type 2 Diabetes Mellitus (T2DM) in the Kingdom of Tonga, little is known of non-communicable disease experiences among adults living in this location. This investigation aimed to explore the barriers and enablers to healthy lifestyle in a group of men and women living with T2DM residing in this Pacific Island nation. Methods This qualitative study consisted of three semi-structured focus groups (n = 16), conducted at the only Tongan Public Hospital located at Nuku'alofa, capital of Tonga (north coast of the island of Tongatapu). Discussions were audio-recorded, transcribed, cross-checked for consistency, and entered into a word processing document for analysis. Thematic analysis was employed to synthesise results. Results Four main themes were identified: (1) Knowledge and Support; (2) Fear and Motivation; 3) Physical and Psychological Environment; and (4) Faith and Culture. Conclusions The qualitative findings from this study will assist the future development and information dissemination of culturally appropriate lifestyle-related for men and women living with T2DM in the Kingdom of Tonga. The need for collaboration between practitioners at the hospital, the church, family members, and local traditional healers is important if the lifestyle-related needs and wants of this group of people are to be met.